UN approval of greenhouse gas emission reduction projects in developing countries: The political economy of the CDM Executive Board - Florens Flues; Axel Michaelowa; Katharina Michaelowa (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
The approval of methodologies and individual projects in the context of the Kyoto Protocol's Clean Development Mechanism (CDM) is often an issue of national interest. Decisions of the CDM Executive Board (EB) can thus be expected to be highly politicized. Based on data for about 250 methodologies and about 1000 projects discussed by the EB so far, this paper provides a first econometric analysis of this hypothesis. The results suggest that indeed, along with formal quality criteria, political-economic variables determine the final EB decision. This is most clearly the case for decisions on CDM projects which are far less transparent than those on CDM methodologies. In particular, EB membership of the country or countries concerned raises the chances of a project to be approved. Moreover, clearly, with rising numbers of methodologies and projects, EB decision making has become stricter over time.
Keywords: Q25; O19; 330; International climate policy; CDM; political economy; rational choice; international organization